Mature Dendritic Cells May Promote High-Avidity Tuning of Vaccine T Cell Responses - Kumbhari, Adarsh; Egelston, Colt A.; Lee, Peter P.; Kim, Peter S. (Frontiers in Immunology, 2020)
Therapeutic vaccines can elicit tumor-specific cytotoxic T lymphocytes (CTLs), but durable reductions in tumor burden require vaccines that stimulate high-avidity CTLs. Recent advances in immunotherapy responses have led to renewed interest in vaccine approaches, including dendritic cell vaccine strategies. However, dendritic cell requirements for vaccines that generate potent anti-tumor T-cell responses are unclear. Here we use mathematical modeling to show that counterintuitively, increasing levels of immature dendritic cells may lead to selective expansion of high-avidity CTLs. This finding contrasts with traditional dendritic cell vaccine approaches that have sought to harness ex vivo generated mature dendritic cells. We show that the injection of vaccine antigens in the context of increased numbers of immature dendritic cells results in a decreased overall peptide:MHC complex load that favors high-avidity CTL activation and expansion. Overall, our results provide a firm basis for further development of this approach, both alone and in combination with other immunotherapies such as checkpoint blockade.